Reading Genesis - Robinson, Marilynne (Farrar, Straus and Giroux, 2024)
For generations, the book of Genesis has been treated by scholars as a collection of documents, by various hands, expressing different factional interests, with borrowings from other ancient literatures that mark the text as derivative. In other words, academic interpretation of Genesis has centered on the question of its basic coherency, just as fundamentalist interpretation has centered on the question of the appropriateness of reading it as literally true. Both of these approaches preclude an appreciation of its greatness as literature, its rich articulation and exploration of themes that resonate through the whole of Scripture. Marilynne Robinson's Reading Genesis, which includes the original text, is a powerful consideration of the profound meanings and promise of God's enduring covenant with man. This magisterial book radiates gratitude for the constancy and benevolence of God's abiding faith in Creation.